New Insights into Duckweed as an Alternative Source of Food and Feed: Key Components and Potential Technological Solutions to Increase Their Digestibility and Bioaccessibility - Krisztina Takács; Rita Végh; Zsuzsanna Mednyánszky; Joseph Haddad; Karim Allaf; Muying Du; Kewei Chen; Jianquan Kan; Tian Cai; Péter Molnár; Péter Bársony; Anita Maczó; et al. (Applied Sciences)
Sustainability is becoming increasingly important in the world we live in, because of the rapid global population growth and climate change (drought, extreme temperature fluctuations). People in developing countries need more sustainable protein sources instead of the traditional, less sustainable meat, fish, egg, and dairy products. Alternative sources (plant-based, such as grains (wheat, rice sorghum), seeds (chia, hemp), nuts (almond, walnut), pulses (beans, lentil, pea, lupins), and leaves (duckweed), as well as mycoproteins, microalgae, and insects) can compensate for the increased demand for animal protein. In this context, our attention has been specifically focused on duckweed—which is the third most important aquatic plant after the microalgae Chlorella and Spirulina—to explore its potential for use in a variety of areas, particularly in the food industry. Duckweed has special properties: It is one of the fastest-growing plants in the world (in freshwater), multiplying its mass in two days, so it can cover a water surface quickly even in filtered sunlight (doubling its biomass in 96 hours). During this time, it converts a lot of carbon dioxide into oxygen. It is sustainable, environmentally friendly (without any pesticides), and fast growing; can be grown in indoor vertical farms and aquaculture, so it does not require land; is easy to harvest; and has a good specific protein yield. Duckweed belongs to the family Araceae, subfamily Lemnoideae, and has five genera (Lemna, Spirodela, Wolffia, Wolffiella, Landolita) containing a total of approximately 36–38 recognised species. Duckweed is gaining attention in nutrition and food sciences due to its potential as a sustainable source of protein, vitamins, minerals, and other bioactive compounds. However, there are several gaps in research specifically focused on nutrition and the bioaccessibility of its components. While some studies have analysed the variability in the nutritional composition of different duckweed species, there is a need for comprehensive research on the variability in nutrient contents across species, growth conditions, harvesting times, and geographic locations. There has been limited research on the digestibility, bioaccessibility (the proportion of nutrients that are released from the food matrix during digestion), and bioavailability (the proportion that is absorbed and utilised by the body) of nutrients in duckweed. Furthermore, more studies are needed to understand how food processing (milling, fermentation, cooking, etc.), preparation methods, and digestive physiology affect the nutritional value and bioavailability of the essential bioactive components in duckweed and in food matrices supplemented with duckweed. This could help to optimise the use of duckweed in human diets (e.g., hamburgers or pastas supplemented with duckweed) or animal feed. More research is needed on how to effectively incorporate duckweed into diverse cuisines and dietary patterns. Studies focusing on recipe development, consumer acceptance, palatability, and odour are critical. Addressing these gaps could provide valuable insights into the nutritional potential of duckweed and support its promotion as a sustainable food source, thereby contributing to food security and improved nutrition. In summary, this article covers the general knowledge of duckweed, its important nutritional values, factors that may affect their biological value, and risk factors for the human diet, while looking for technological solutions (covering traditional and novel technologies) that can be used to increase the release of the useful, health-promoting components of duckweed and, thus, their bioavailability. This article, identifying gaps in recent research, could serve as a helpful basis for related research in the future. Duckweed species with good properties could be selected by these research studies and then included in the human diet after they have been tested for food safety.